Teknik Modelling: Sebuah Alternatif dalam Peningkatan Self Efficacy Akademik - Ade Herdian Herdian; Frischa Meivilona Yendi (Indonesian Counselor Association (IKI), 2019)
Academic self efficacy is a person's belief in his ability to meet academic demands well. Factors that can affect academic self efficacy can be in the form of mastering experiences, experiences of others, social persuasion, and physical and emotional conditions. Low academic self efficacy in students will have a negative impact in the learning process. Therefore we need a way to improve academic self efficacy. One way to improve students' academic self-efficacy is to use modeling techniques in counseling services. This paper will explain modeling techniques as an alternative in improving academic self efficacy. Hopefully this script can be used as a reference.